Employment and continuing vocational training (CVT) in the German Microcensus of the year 2003 - Kai S. Meinke (Kiel Institute for the World Economy (IfW), 2010)
This paper is based on my thesis from the year 2008. It uses the German Microcensus (MC) to study the effects of continuing vocational training (CVT) on employment, the risk of unemployment, and wages. To control for education, profession and heterogeneity in the sectors and industrial branches in Germany individuals are separated into sub-groups. The results of my estimations indicate high returns to continuous vocational training in terms of lower risk to be unemployed, higher chances to be reemployed and higher chances to stay into an existing employment. The results also indicate that repeated short activities in CVT are more beneficial then long activities typically carried out by the German employment agency during the period of the Microcensus 2003.
Keywords: J31; J10; J14; 330; Microcensus; Mikrozensus; Employment; Continuous Vocational Training; Employment Agency; Job Center; Mincer; Human Capital Theory; Duale Berufsausbildung; Weiterbildung; Wirkungsanalyse; Beschäftigungseffekt; Arbeitsplatzsicherung; Lohn; Deutschland